2012
DOI: 10.1210/jc.2012-1159
|View full text |Cite
|
Sign up to set email alerts
|

Reduced mRNA and Protein Expression of Perilipin A and G0/G1 Switch Gene 2 (G0S2) in Human Adipose Tissue in Poorly Controlled Type 2 Diabetes

Abstract: We found reduced mRNA and protein content of Plin and G0S2 and borderline increased ATGL protein in sc AT from poorly controlled type 2 diabetic subjects. This suggests that increased ATGL activity may contribute to the elevated lipolysis and circulating FFA levels in acute insulin withdrawal and metabolic dysregulation in type 2 diabetic patients and that this mechanism may be modifiable.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
24
0
1

Year Published

2012
2012
2017
2017

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(26 citation statements)
references
References 20 publications
1
24
0
1
Order By: Relevance
“…The fi nding that G0S2 mRNA and protein expression is reduced in adipose tissue of type 2 diabetic humans suggests that enhanced ATGL activity may contribute to elevated lipolysis and plasma FA levels in type 2 diabetic patients ( 20 ). Considering the nutritional and hormonal regulation of G0S2, downregulation of this protein could represent one of the underlying mechanisms causing increased lipolysis in the insulinresistant state.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The fi nding that G0S2 mRNA and protein expression is reduced in adipose tissue of type 2 diabetic humans suggests that enhanced ATGL activity may contribute to elevated lipolysis and plasma FA levels in type 2 diabetic patients ( 20 ). Considering the nutritional and hormonal regulation of G0S2, downregulation of this protein could represent one of the underlying mechanisms causing increased lipolysis in the insulinresistant state.…”
Section: Discussionmentioning
confidence: 99%
“…Accordingly, the antilipolytic hormone insulin increases G0S2 expression in murine 3T3 cells, whereas stimulation of lipolysis by ␤ -adrenergic agonists and tumor necrosis factor-␣ has the opposite effect ( 13,19 ). Importantly, a recent report demonstrated that G0S2 mRNA and protein expression is reduced in adipose tissue of type 2 diabetic humans, indicating that enhanced ATGL activity contributes to elevated lipolysis and plasma fatty acid (FA) levels in type 2 diabetes ( 20 ).…”
Section: Sequence Analysismentioning
confidence: 99%
“…Similarly, increased FFA mobilization was found in type 2 diabetic patients following 16 h of hypoinsulinemia (15). Notably, no change was found in adipose tissue HSL phosphorylation while G0S2 was decreased, clearly suggesting a distinct increase in basal lipolysis (15). Importantly, G0S2 does indeed regulate ATGL activity in human fat cells (9), and fasting-induced reductions in G0S2 expression have also been found in adipose tissue from birds (16) and pigs (17), indicating that this regulatory mechanism is highly conserved.…”
mentioning
confidence: 73%
“…Indeed, it has previously been shown in humans that elevated FFA mobilization during prolonged fasting is associated with a substantial decrease in G0S2 in adipose tissue (14). Similarly, increased FFA mobilization was found in type 2 diabetic patients following 16 h of hypoinsulinemia (15). Notably, no change was found in adipose tissue HSL phosphorylation while G0S2 was decreased, clearly suggesting a distinct increase in basal lipolysis (15).…”
mentioning
confidence: 84%
“…Yet, it has been shown that human G0S2 inhibits human ATGL in a dosedependent manner [20]. Furthermore, human G0S2 is downregulated in WAT by fasting and in individuals with poorly controlled type 2 diabetes [21,22]. Unfortunately, to date, Fig.…”
mentioning
confidence: 99%